EVALUASI KESESUAIAN LAHAN PERMUKIMAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KECAMATAN SEKADAU HULU KABUPATEN SEKADAU - Wiranto, Markus; Buwono, Sri; Christanto, L. M. Hari (Universitas Tanjungpura, 2023)
This study aims to determine the incompatibility of using existingresidential land toward regional spatial planning, and land suitabilityfor residential areas in Sekadau Hulu District, Sekadau Regency. Themethod that used in this study is quantitative method which usedspatial approach, remote sensing, and geographic informationsystem (GIS). The source of the data for this study are fromgovernment agencies and internet access which provided spatial dataand land suitability criteria. The finding of this study showed that,(1) the incompatibility of using existing residential land towardregional spatial planning is 355,02 ha. The next step after knowingthe extent of the incompatibility between the existing land use andthe regional spatial planning is build a map of the slope, flood,drainage, gravel, and soil texture. The results of the overley ofseveral land suitability criteria for the settlements show (2) a verysuitable area (S1) is 45,150.37 Ha, a suitable area (S2) is 34,311.4Ha, a marginally suitable area (S3) is 3,393.03 Ha. , and the area thatis not suitable (N) is 75.72 Ha.